Novel axially di-substituted natural, cationic and zwitter ionic silicon phthalocyanine derivatives: Synthesis, characterization, sono-photochemical properties - Messaoudi, Hiba; Atmaca, Goknur Yasa; Erdogmus, Ali (ELSEVIER, 2024)
This study focuses on investigating the sono-photophysicochemical properties of recently synthesized and characterized di-axially substituted silicon phthalocyanine complexes, incorporating schiff-base groups and zwitter ions, imparting novel features and potential therapeutic applications. Specifically, our research focused on evaluating the suitability of these complexes for photodynamic therapy (PDT), sonodynamic therapy (SDT), and the emerging field of sono-photodynamic therapy (SPDT). The characterization process involved the application of various analytical techniques, including UV-Vis spectroscopy, infrared (FT-IR) spectroscopy, and proton nuclear magnetic resonance (1H NMR) spectroscopy. Experimental results displayed highly promising outcomes, revealing that the synthesized sensitizers exhibited exceptional efficiency in generating reactive oxygen species, a critical attribute necessary for effective therapeutic interventions. This finding significantly contributes to the development of novel therapeutic agents with enhanced photodynamic and sonodynamic properties. Harnessing the power of light and sound simultaneously through sonophotodynamic therapy offers a unique and synergistic approach, potentially amplifying the therapeutic efficacy of these complexes. The combination of sonochemical and photochemical applications produced better results, for the studied compounds, the quaternized complexes (cationic compounds) showed the higher result. Overall, the results suggest that SPDT is a promising combination therapy for cancer treatment.
Keywords: Photodynamic therapy; Sono-photodynamic therapy; Silicon phthalocyanine; Schiff -base; Zwitter ions; SCHIFF-BASE; RECENT PROGRESS; THERAPY; Chemistry